1987
DOI: 10.1007/bf01782047
|View full text |Cite
|
Sign up to set email alerts
|

Vascular recanalizing techniques in the hind brain circulation

Abstract: Percutaneous transluminal angioplasty (PTA) was performed in 45 patients with a manifest subclavian steal syndrome. Thirty-five of those patients were subjected to follow up examinations over a period of 6 to 18 months. Five patients suffered from severe restenosis and were treated again. Two thirds of the patients benefited from the treatment. PTA of the proximal vertebral artery was performed in 15 patients with bilateral occlusive lesions of the extracranial vertebral arteries. In 13 of these cases the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…92 Coronary and intracranial balloon catheters and stents have been applied anecdotally to the treatment of refractory acute cerebral artery occlusion with stroke with some success since 1987. 16 In a series of 13 patients at a single Chinese center who underwent combined mechanical thrombectomy with angioplasty and stenting, 46% had a good functional outcome, with an mRS score of at least 2 at 90 days. 92 In the anterior circulation, for patients with acute atherosclerotic occlusion, it has even been suggested that primary angioplasty and stenting may be superior to thrombectomy.…”
Section: Angioplasty and Stent Angioplastymentioning
confidence: 99%
See 1 more Smart Citation
“…92 Coronary and intracranial balloon catheters and stents have been applied anecdotally to the treatment of refractory acute cerebral artery occlusion with stroke with some success since 1987. 16 In a series of 13 patients at a single Chinese center who underwent combined mechanical thrombectomy with angioplasty and stenting, 46% had a good functional outcome, with an mRS score of at least 2 at 90 days. 92 In the anterior circulation, for patients with acute atherosclerotic occlusion, it has even been suggested that primary angioplasty and stenting may be superior to thrombectomy.…”
Section: Angioplasty and Stent Angioplastymentioning
confidence: 99%
“…Recommendations follow the American College of Cardiology/American Heart Association (ACC/ AHA) classification of recommendation and level of evidence. 16…”
Section: Introductionmentioning
confidence: 99%